Export performance, invoice currency, and heterogeneous exchange rate pass-through - Richard Fabling; Lynda Sanderson (New Zealand Government, The Treasury, 2013)
Using comprehensive, shipment-level merchandise trade data, we examine the extent to which New Zealand exporters maintain stable New Zealand dollar prices by passing on exchange rate changes to foreign customers. We find that the extent to which firms absorb exchange rate fluctuations in the short run is significantly related to both invoice currency choice and exporter characteristics when these are analysed separately. However, when jointly accounted for, the role of exporter characteristics largely disappears. That is, some firm types are more inclined to invoice in the New Zealand dollar, while others use either the importer or a third currency. In the short run, this translates into differences in exchange rate pass through because of price rigidity in the invoice currency. Differences across invoice currencies diminish, but do not disappear, over time as prices adjust to reflect bilateral exchange rate movements.
Keywords: D21; F14; F31; 330; Exchange rate pass-through; Firm performance; Exchange Rate Pass-Through; Handelseffekt; Neuseeland